1999
DOI: 10.1161/01.res.84.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I Gene Knockout

Abstract: —Troponin I is a subunit of the thin filament–associated troponin-tropomyosin complex involved in calcium regulation of skeletal and cardiac muscle contraction. We deleted the cardiac isoform of troponin I by using gene targeting in murine embryonic stem cells to determine the developmental and physiological effects of the absence of this regulatory protein. Mice lacking cardiac troponin I were born healthy, with normal heart and body weight, because a fetal troponin I isoform (identical to slow skeletal tropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
99
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 44 publications
9
99
0
Order By: Relevance
“…This functional importance might have been responsible for the ssTnT gene remaining closely linked to the upstream cTnI gene during evolution, because a destruction of either the 3Ј-coding exons of the cTnI gene or the 5Ј-enhancer region of the ssTnT gene would cause infantile lethality (5,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This functional importance might have been responsible for the ssTnT gene remaining closely linked to the upstream cTnI gene during evolution, because a destruction of either the 3Ј-coding exons of the cTnI gene or the 5Ј-enhancer region of the ssTnT gene would cause infantile lethality (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…The genotyping of the double transgenic offspring was performed on genome DNA isolated from tail biopsies using PCR, and the compensation for the loss of endogenous cTnI by cTnI-ND in cardiac muscle was confirmed by Western blotting as described (7,9) (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the effects of MuRF1 on contractility are consistent with the reported effects of loss of troponin I function. Deletion of troponin I results in decreased contractility and cardiac dysfunction in mice (33), and a recessive mutation in troponin I that disrupts assembly of the troponin complex also results in a contractility defect in humans (34). It is tempting to speculate that disassembly of sarcomeres by molecules such as MuRF1 may be a maladaptive response that contributes to wall thinning and contractile dysfunction in dilated cardiomyopathies.…”
Section: Discussionmentioning
confidence: 99%
“…The protein isoforms and their corresponding mRNAs follow the same pattern of accumulation, suggesting that the transition in troponin expression is regulated at the level of gene transcription (45). A mouse model lacking CTnI demonstrated that a fetal TnI isoform that is identical to STnI, compensated for the absence of CTnI up to 15 days after birth and around day 18, the mice died of acute heart failure (46). This suggested that some form of TnI is required for normal cardiac function and survival.…”
Section: Troponin Imentioning
confidence: 98%